Constitutionalism in Indonesia: An Islamic Governance Legal Perspective - Fikri Hadi; Farina Gandryani; Innocent Muramuzi; Tayyaba Razzaq (CV. Era Digital Nusantara, 2023)
Abstract: Islam is the most followed religion in Indonesia, making Indonesia contains the largest Muslim population of all countries in the world. However, Indonesia is not a religion state. This has become an issue in several Muslim groups in Indonesia, whether it is permissible to have a state under the Republic of Indonesia based on their beliefs. Purpose: This paper will explain the relationship between Islam and The State of Indonesia and the study of Islamic government law related to the Indonesian government. Design/Methodology/Approach: This research is qualitative. The approach used is statute, conceptual, and hermeneutics, while the assessment method used is comparative. Findings: The system of government of Indonesia has a close relationship to the principles and substance of Islamic law. Although the State of Indonesia is not an Islamic state, Indonesia is also not a secular state, which separates religion and state. From the Islamic government law’s perspective, it’s called tamyiz or proportional. Indonesia takes Islam in the principles of state proportionally. Therefore, The State of Indonesia is not contrary to the principles of Islam. Originality/value: Numerous studies have been undertaken to examine the correlation between religion and the government in Indonesia. This article builds upon the earlier research conducted by other scholars. This article affirms that the Indonesian State is not in conflict with Islam.